1997
DOI: 10.12968/bjtr.1997.4.7.14417
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy and forensic addictive behaviours

Abstract: This paper briefly outlines the role of occupational therapy in assessing and treating patients with the tripartite problems of mental disorder, dangerousness and an addictive behaviour. The first unit dedicated to the management of such patients within conditions of high security was opened in Broadmoor Hospital in 1995. It is a 25-bedded male inpatient ward. This article focuses on occupational therapy in this unit, the forensic addictive behaviours unit, but many of the issues discussed apply to patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…This is in line with the previously described time use for addicts, where time may revolve around a lifestyle of substance misuse and seeking ways to fund and maintain their addiction (21,22). Research also suggests the need for people with addictions to redefine the meanings attached to their time use (21). This need is also identified in the present study where the participants created a broader time perspective during their transitions in order to be able to create meaning for their actions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is in line with the previously described time use for addicts, where time may revolve around a lifestyle of substance misuse and seeking ways to fund and maintain their addiction (21,22). Research also suggests the need for people with addictions to redefine the meanings attached to their time use (21). This need is also identified in the present study where the participants created a broader time perspective during their transitions in order to be able to create meaning for their actions.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, for addicts, time may revolve around a lifestyle of substance misuse and seeking ways to fund and maintain their addiction (21,22). Research suggests the need for people with addictions to redefine the meanings attached to their time use.…”
Section: Leaving Homelessness and Addiction 161mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the therapeutic interventions offered by occupational therapists in a forensic setting occur in groups (Duncan et al 2003) and it is usually the occupational therapist who coordinates the group activity programme on the ward (Freeman 1982, Chacksfield and Forshaw 1997, Flood 1997). However, in the only study that elicited participants' views on group programmes in Australia, Farnworth et al (2004) reported that the participants described many of the groups as boring and a waste of time, or that they had grown tired of attending groups after long periods of detention.…”
Section: Occupational Therapy Interventionsmentioning
confidence: 99%
“…Within the occupational therapy literature, authors have described working with a variety of specialised client groups, including female offenders (Lloyd 1987e), sexual offenders (Lloyd 1987b), young offenders (Paulsen 1980), offenders with AIDS (Schindler 1990), prisoners with special needs (Whiteford 1995(Whiteford , 1997 and those with the tripartite problem of mental disorder, offending behaviour and addictive behaviour (Chacksfield and Forshaw 1997). Authors have also noted an overrepresentation of particular cultural groups where they work, including African-Caribbean patients in the UK (Garner 1995) and Maori and Pacific Islanders in New Zealand (Tse 1990).…”
Section: Issues Having An Impact On Occupational Therapy Interventionmentioning
confidence: 99%